Evaluation of the GENE-UP® EHEC Detection Method for the Detection of Enterohemorrhagic E. coli in Select Foods: Collaborative Study: First Action Method 2020.06. (19th April 2021) - Johnson, Ronald; Mills, John; Pittet, Jean-Louis; Rannou, Maryse; Bird, Patrick
Abstract: Background: The GENE-UP ® EHEC assay ( Performance Tested Method SM 121806) is a real-time PCR molecular detection method that utilizes fluorescence resonance energy transfer proprietary hybridization probes for the rapid detection of enterohemorrhagic Escherichia coli (EHEC) in select foods. Objective: The purpose of this validation was to evaluate the method's interlaboratory performance and submit the results to AOAC INTERNATIONAL for adoption as a First Action Official Method of Analysis SM for the detection of EHEC in select foods. Method: The GENE-UP method was evaluated in a multi-laboratory study as part of the MicroVal VALIDATION certification process using unpaired test portions for one food matrix, raw ground beef (85% lean). Collaborators evaluated the candidate method using either an automated or manual lysis procedure. The candidate method was compared to the ISO/TS 13136:2012 method. Data from 17 participants from 15 laboratories throughout the European Union were evaluated. Three levels of contamination were evaluated: a non-inoculated control level (0 CFU/test portion), a low contamination level (∼1 CFU/test portion), and a high contamination level (∼10 CFU/test portion). Data from the study were analyzed according to the probability of detection (POD) statistical model. Results: The difference in laboratory probability of detection (dLPODC ) values with 95% confidence interval between the candidate and reference method results were –0.01 (–0.04, 0.02), 0.23 (0.07, 0.39), and 0.06 (0.01, 0.12) for the non-inoculated, low, and high contamination levels, respectively. Conclusions: For the candidate method, values obtained for repeatability and reproducibility were similar to the reference method and indicated minimal variation between samples or between laboratories. No discrepant results (false positive or false negative) were observed for each contamination. A statistical difference was calculated between the candidate and reference method at the low and high inoculation levels, with the candidate method detecting a higher number of positive samples indicating a higher sensitivity than the reference method. No differences in the recovery of the target analyte were observed between the manual and automated lysis procedures. Highlights: The GENE-UP EHEC Detection Method provides end users a rapid, easy-to-use workflow for the detection of EHEC in food matrixes.